ARTISTIC SEARCHES IN THE FIELD OF THE HERO AND CONTENT IN THE POETRY OF A. AKHMATOVA - Chjen Elena Vitalievna; Khodjibekova Mushtariy (Journals Park Publishing, 2022)
The article deals with one of the most important problems in the work of Anna Akhmatova - Anna Akhmatova's artistic search in the field of genre form, the search for the hero, content, means of expression.
Keywords: Genre searches, lyrical hero, A. A. Akhmatova,